PENGEMBANGAN PRODUK TEMPE DI UKM "TEMPE TITIK 2" - Solikhi, Mohammad Whildhan; Sumantika, Arsyad (Computer Science and Industrial Engineering, 2024)
Tempe is one of the original Indonesia folk foods that is starting to become popular in the world. The tempe processing industry is classified as a micro, small and medium industry. In the face of increasingly tight business competition, companies are required to continue to develop in order to be able to face existing competition. SMEs in Batam City, precisely in Kav Sei Lekop Kec. Sagulung, a business operating in the food processing industry, uses soybeans as raw materials which are processed into tempeh. The aim of this research is to analyze the development of tempeh products using the QFD (Quality Function Deployment) method. The subjects of this research are the parties involved in Tempe Titik 2 UKM and their consumers. Determination of sample size using the Slovin formula. Based on the results of the data and analysis, it is known that there are 8 attributes that consumers want, while the HOQ (House of Quality) results on the customer needs indicator obtained the largest value, namely the value of tempeh availability. product, while the functional indicator that obtains the greatest value is the form value. and the size of the tempeh product is as expected and UKM "Tempe Point 2" must add or change the shape and size of the tempe product, in order to be able to compete in the market and meet consumer demand.